2016
DOI: 10.14582/duzgef.746
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Akademik Öz-Yeterlikleri ve Matematik Öğretimine Yönelik Öz-Yeterliklerinin Bazı Değişkenler Açısından İncelenmesi

Abstract: Bu araştırmanın amacı, öğretmen adaylarının akademik öz-yeterlikleri ile matematik öğretimine yönelik özyeterliklerinin bazı değişkenler açısından incelenmesidir. Araştırmada ilişkisel tarama modeli kullanılmıştır. Araştırmanın katılımcılarını bir devlet üniversitesinde Eğitim Fakültesi Okul Öncesi, Sınıf ve İlköğretim Matematik Öğretmenliği programında öğrenim gören 3. sınıf öğrencileri arasından gönüllülük esasına göre seçilen 188 öğretmen adayı oluşturmaktadır. Araştırmanın verileri "Akademik Öz-yeterlik Öl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
2
0
9
Order By: Relevance
“…Hence, it can be said that teacher candidates with low mathematics achievement have low academic self-efficacy perceptions and those with high mathematics achievement have high academic self-efficacy perceptions. This may be a reflection of the positive attitude of the teacher candidates who have high level of mathematics achievement and see themselves as academically competent in dealing with mathematical concepts, trusting their abilities This result of the research coincides with the results of the studies conducted by Yağcı and Aksoy (2015), Yenilmez (2016). In these studies, it was determined that when academic achievement of teacher candidates was high, their academic self-efficacy was also higher.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hence, it can be said that teacher candidates with low mathematics achievement have low academic self-efficacy perceptions and those with high mathematics achievement have high academic self-efficacy perceptions. This may be a reflection of the positive attitude of the teacher candidates who have high level of mathematics achievement and see themselves as academically competent in dealing with mathematical concepts, trusting their abilities This result of the research coincides with the results of the studies conducted by Yağcı and Aksoy (2015), Yenilmez (2016). In these studies, it was determined that when academic achievement of teacher candidates was high, their academic self-efficacy was also higher.…”
Section: Discussionsupporting
confidence: 84%
“…In the literature review, it was found that many studies were conducted on teacher candidates' self-efficacy and academic self-efficacy beliefs (Çuhadar, Gündüz & Tanyeri, 2013;Özsüer, et al, 2011;Tunca & Alkın-Şahin, 2014;Fırat, 2010;Yenilmez, 2016;Ekici, 2012;Oğuz, 2012;Yağcı & Aksoy, 2015, Yalmancı & Aydın, 2014Tabancalı & Çelik, 2013;Azar, 2010;Korucu & Çınar, 2017;Alemdağ et al, 2014;Aydın et al, 2014;Demirtaş et al, 2011;Saracaloğlu et al, 2013;Güzel, 2017;Ünlüet al, 2017;Donmuş et al, 2017;Altunç ekiç et al, 2005;Erdem, 2008;Senemoğlu et al, 2009;Taşkın & Hacıömeroğlu, 2010;Yaşar et al, 2006;Zajacova et al, 2005;Bonk, 2004;Schunk & Pajares, 2002;Taylor, 2014;Bandura, 1997;Pajares, 1996;Bong & Clark, 1999;Gore, 2006). However, there are a limited number of studies on academic self-efficacy beliefs of mathematics teacher candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Öğretmen adaylarının matematik öğretimine yönelik özyeterlik inançlarının 1., 2., ve 3. sınıflarda orta düzeyde, 4. sınıfta ise yüksek düzeyde olduğu belirlenmiştir. Yapılan araştırmalar incelendiğinde, bazı araştırmalarda matematik öğretimine yönelik öz-yeterliklerinin genel olarak orta düzeyde olduğu sonucuna ulaşılmış (Doruk ve Kaplan, 2012;Yenilmez, 2017), bazı araştırmalarda ise öğretmen ve öğretmen adaylarının matematik öğretimine yönelik özyeterlik inançlarının yüksek olduğu belirlenmiştir (Dede, 2008;Şahin, Gökkurt ve Soylu, 2014). Öğretmenlerin özyeterlik inançları matematiği etkili bir şekilde öğretmelerinde oldukça önemli (Dede, 2008) olduğundan, öğretmen adaylarının lisans eğitimlerinin sonunda matematik öğretimine yönelik özyeterlik inançlarının yüksek çıkması beklenmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…In the mentioned periods, it is seen as an important research subject of self-efficacy of mathematics teaching teachers who will conduct mathematics courses as an indicator of how they feel enough about mathematics teaching. Thus, if the said self-efficacy is low, necessary measures can be taken in the pre-service period and there will be no self-confidence problem in mathematics teaching after taking office ( Yenilmez, 2017). A teacher who is not competent in his/her field cannot be expected to give confidence to his/her students and to create an authority based on respect.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%